ANALISIS DAMPAK MEDIA SOSIAL DAN STRATEGI CONTENT MARKETING TERHADAP PENINGKATAN JUMLAH PASIEN KLINIK ANAK SPC MEDAN JOHOR - Suryani, Wan (Universitas Lancang Kuning, 2025)
This study aims to analyze the impact of social media and content marketing strategies on increasing the number of patients at SPC Children's Clinic Medan Johor. The background of this research is the development of information technology that allows social media and content marketing to be an interactive tool to increase public engagement and trust in health services. The study used a quantitative approach with a survey method, involving 100 respondents who were parents of patients. Analysis was conducted using multiple linear regression to test the effect of social media and content marketing individually and simultaneously on increasing the number of patients. The results showed that social media and content marketing significantly influenced the increase in patient numbers. The social media-based digital marketing strategy, especially through Instagram and TikTok, succeeded in attracting audience attention through educational, informative, and interactive content, thus building trust and community engagement. The conclusion of this study confirms that optimizing social media and content marketing strategies can increase the effectiveness of health service promotion, strengthen relationships with the community, and significantly increase the number of patients.